Classification internationale: modèle de développement humain - processus de production du handicap (MDH-PPH) - Cloutier, Chantal; Poulin, Marie-Michelle; Sauvé, Méric; Fougeyrollas, Patrick; Cloutier, René; Bergeron, Hélène; Réseau international sur le processus de production du handicap (RIPPH, Réseau international sur le Processus de production du handicap, 2018)
La Classification internationale : Modèle de Développement humain – Processus de production du handicap (2018) comprend le schéma conceptuel du MDH-PPH, les définitions des domaines conceptuels « habitudes de vie », « facteurs environnementaux » et « facteurs personnels » et leurs différentes nomenclatures. Ce document de référence se révèle utile pour classer l’information disponible de manière cohérente en respectant le principe d’exclusion mutuelle des concepts, central à l’approche du MDH-PPH.
Keywords: EDI; approches et analyses; capacitisme; cours; discipline; médecine; premier cycle; santé; sciences; sex1920; systèmes d'oppressions; thématiques; études critiques du handicap

Reproductive and Sexual Health of People with Physical Disabilities: A Metasynthesis - Nguyen, Thi Tu An; Liamputtong, Pranee; Monfries, Melissa (Sexuality and Disability : A Journal Devoted to the Psychological and Medical Aspects of Sexuality in Rehabilitation and Community Settings, 2016)
This article provides an overview on reproductive and sexual health of people with physical disabilities in developed and underdeveloped countries from 1995 to 2011. Based on the metasynthesis approach, the authors reviewed 15 qualitative studies. These studies were searched using Medline, CINAHL, CINAHL (health), ProQuest Central, Google Scholar, Cochrane, Embase, Informit Health, Sciences Direct, Pubmed, Pubmed Health, AAHD (abstracts), ProQuest Journal (sexuality and disability) and were also manually searched. All studies were judged on their qualities using the Critical Appraisal Skills Programme. Reproductive health, sexual attractiveness and experiences, reproductive and sexual health knowledge, and dealing with reproductive and sexual health issues were four main themes that emerged from these studies. This paper proposes a new model to explain the factors that impacted the reproductive and sexual life of people with physical disabilities: internal and external factors. Implications for health and social care are discussed in light of the findings.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; approches et analyses; capacitisme; care; cours; discipline; justice reproductive; médecine; métasynthèse; premier cycle; psychologie; périodes historiques; ressource en ligne; santé; sciences; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; travail social

It's in Our Blood: Indigenous women's knowledge as a critical path to women's well-being - Gaudet, Janice Cindy; Caron-Bourbonnais, Diane (AlterNative: An International Journal of Indigenous Peoples, 2015)
The research reported in this article sought to shed light on the North, Central and South American indigenous moon time teachings related to the menstrual cycle of women. The historical institutionalization, medicalization and colonization of indigenous women's practices have devalued and almost destroyed this knowledge. This study explored the question of whether or not lost indigenous knowledge of women's power can be reclaimed for women's health and well-being. A qualitative participatory research methodology was adopted, based on an indigenous paradigm and scholarly rigour and including protocols acceptable to an Ojibwe grandmother, Isabelle Meawasige, who shared her knowledge and experience. The experiential knowledge gained and the meanings expressed by female participants in a circle sharing facilitated by the principal author are presented and discussed. The results of this research reveal optimistic possibilities to co-create health and well-being for the participants, grounded in what is both visible and invisible within indigenous women's culture.
Keywords: amériques; approches et analyses; care; cours; cycle menstruel; discipline; féminisme autochtone; justice reproductive; médecine; médicalisation; pol4105; premier cycle; règles; régions géographiques; santé; sciences; sciences de la santé; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail social

Race, gender, class, sexuality (RGCS) and hypertension - Veenstra, Gerry (Social Science & Medicine, 2013)
Informed by intersectionality theory, a tradition that theorizes intersecting power relations of racism, patriarchy, classism and heterosexism, this paper investigates the degree to which race, gender, class and sexuality manifest distinct and interconnected associations with self-reported hypertension in nationally-representative survey data from Canada. Binary logistic regression is used to model the main effects of, and interactions between, race, gender, education, household income and sexual orientation on hypertension, controlling for age, using data from the 2003 Canadian Community Health Survey (n = 90,310). From a main effects (‘additive’) perspective, Black respondents, respondents with less than high school and poorer respondents were significantly more likely than White respondents, university-educated Canadians and wealthier Canadians, respectively, to report hypertension. However, the interactive models indicate that the additive models were poor predictors of hypertension for wealthy Black men, wealthy South Asian women, women with less than a high school diploma and wealthy bisexual respondents, who were more likely than expected to report hypertension, and for poor Black men, poor South Asian women, poor South Asian men and women with a university degree, who were less likely than expected to report hypertension. It appears that, with regard to blood pressure at least, Canadians experience the health effects of education differently by their genders and the health effects of income differently by their identities defined at the intersection of race and gender. This study provides empirical support for the intersectional approach to cardiovascular health inequalities by demonstrating that race, gender, class and sexuality cannot be disentangled from one another as predictors of hypertension.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; capitalisme; discipline; hétérosexisme; intersectionnalité; médecine; patriarcat; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; santé cardiovasculaire; sciences; sexisme; systèmes d'oppressions; thématiques

Minorités sexuelles, Internet et santé - Lévy, Joseph J. (Presses de l'Université du Québec, 2011)
Les nouvelles technologies de communication, et notamment Internet, ont transformé à la fois les stratégies relationnelles et la transmission et le partage des informations dans toutes les sphères de la vie, incluant le domaine de la santé. Pour les minorités sexuelles qui sont confrontées à de multiples formes de discrimination et de marginalisation, Internet est devenu un puissant moyen de s’organiser, d’informer et d’intervenir dans le champ de la santé. Les associations et organismes communautaires ciblant ces populations proposent aujourd’hui un ensemble de sites et de stratégies de soutien et d’intervention. Ces outils synchrones et asynchrones disponibles en ligne visent l’amélioration de la santé mentale et physique, des relations interpersonnelles et la prévention des ITSS et du VIH/sida. Par contre, les usages qui varient en fonction des populations LGBT peuvent aussi concourir à la prise de risques et à des formes de dépendance. Afin de mieux comprendre les enjeux entourant les usages d’Internet et la santé, cet ouvrage, réalisé grâce à l’appui de l’équipe pancanadienne Sexualités et genres ;: vulnérabilité et résilience (SVR), regroupe les contributions de chercheurs de l’équipe qui ont effectué des travaux sur Internet et la santé ainsi que d’intervenants impliqués dans des organismes communautaires, qui utilisent des sites Internet à des fins de réseautage, de transfert d’informations et d’interventions en ligne dans les contextes québécois et canadien.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; cours; discipline; hétérosexisme; internet; militance; médecine; organisme communautaire; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; réseaux sociaux; santé; sciences de la santé; sciences humaines; sexualité; soc2014; système médical; systèmes d'oppressions; thématiques; travail social